2019
DOI: 10.5194/bg-2018-520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subaqueous speleothems (Hells Bells) formed by the interplay of pelagic redoxcline biogeochemistry and specific hydraulic conditions in the El Zapote sinkhole, Yucatán Peninsula, Mexico

Abstract: <p><strong>Abstract.</strong> Unique bell-shaped underwater speleothems were recently reported from the deep (~ 55 m) meromictic El Zapote sinkhole (cenote) on the Yucatán Peninsula, Mexico. The local diving community has termed these speleothems as Hells Bells because of their shape and appearance in a lightless environment in ~ 28–38 m water depth above a sulfidic halocline. It was als… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Previous studies proposed the redoxcline, which overlaps with the turbid layer, as the water layer in which calcite is precipitated (Ritter, 2020; Ritter et al, 2019). Here, we conducted a specific study that targeted the hydrogeochemical profile of the turbid layer at the time of microbiome sampling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies proposed the redoxcline, which overlaps with the turbid layer, as the water layer in which calcite is precipitated (Ritter, 2020; Ritter et al, 2019). Here, we conducted a specific study that targeted the hydrogeochemical profile of the turbid layer at the time of microbiome sampling.…”
Section: Resultsmentioning
confidence: 99%
“…However, this hypothesis is solely based on the observation of structures in the cave ceiling that were interpreted as bubble trails. Prior to that, Ritter et al (2019) reported detailed hydrogeochemical profiles, chemical and optical analyses on Hells Bells carbonate speleothems and SEM analyses on filtrates of the turbid layer of El Zapote. They showed that Hells Bells most likely grow in the lowermost freshwater body as indicated by uranium isotopes of Hells Bells carbonate samples and the comparison of Mg/Ca ratios of the water body and Hells Bells carbonates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations